Samsung galaxy tab application sketch book - Kaplan, Dean (Berkeley, California Apress, 2011)
Think you have the next great Samsung galaxy tab app idea? The Samsung galaxy tab application sketch book is an essential tool for any aspiring Android developer. This sketch book makes it easy to centralize and organize your ideas, featuring enlarged Samsung Galaxy Tab templates to write on. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes and document the app name and screen name.  This book is an invaluable tool for bringing your next great Galaxy tablet app idea to life
Electronic reproduction.
Keywords: Android (Electronic resource).; Application software -- Development